Addressing the Oncologist Shortage in Latin America: Insights From a Survey of Medical Oncology Fellowship Programs - Mauricio Zegarra-López; Alejandro Aranda-Gutierrez; Jose Felipe Muñoz Lozano; Cynthia Villarreal-Garza (JCO Global Oncology)
PURPOSELimited information exists about medical oncology fellowship programs in Latin America. Our study aimed to clarify unknowns, with the goal of identifying areas for improvement and potential expansion of fellowships.MATERIALS AND METHODSSixteen medical oncologists, each from a different Latin American country, were surveyed using an online questionnaire. Descriptive statistics were used to summarize the collected variables.RESULTSIn total, 232 fellowship programs exist in the surveyed nations, of which 444 medical oncologists graduate every year. Only Argentina, Brazil, Chile, Mexico, and Peru have more than five active fellowship programs. Honduras and Nicaragua did not report any fellowship programs. These nations—along with Colombia, Ecuador, El Salvador, Guatemala, and Peru—depend on foreign education for the training of their medical oncologists. Only one of every 50 medical graduates pursues a career path in medical oncology, and a mere 2.2% of internal medicine residents transition into the field. Nearly half of the data were collected through word of mouth, as many countries lack official, publicly accessible sources for some of the variables studied.CONCLUSIONThis study serves as a pioneering effort that future research groups can build upon. We believe that addressing the shortage of medical oncologists in Latin America by increasing the number of locally trained fellows is the most effective way to swiftly and sustainably improve cancer outcomes.